Pengaruh Permainan Tradisional Dalam Mengembangkan Kecerdasan Jamak Anak Usia Dini Pada PAUD Di Kota Mataram - Warni Djuwita; Mohammad Fakhri (UIN Sultan Maulana Hasanuddin Banten, 2019)
This study aims to explain the influence of traditional games in developing plural intelligence in early childhood. Playing is fun, learning through games allows a child to learn in a natural way, where excitement creates optimal enthusiasm. Learning does not have to be done seriously and indoors, with full concentration, but can be done by playing adapted to the stages of development, abilities and behavior of children. Because children will play in the most appropriate way for the things they have to learn. This research is a qualitative research. Subjects were 25 early childhood children with two traditional games, Long se and Congklak. Data collection is done by observation, interviews, and documentation. Based on the results of the study it can be concluded that traditional games affect the development of plural intelligence of early childhood students. This is based on the results of the analysis of research data using the t test contained in the simple regression test obtained tcount = 3.755 while ttable = 2.069 at the significance level α = 0.05 with dk = 23 because it was obtained (tcount> t table). Keywords: traditional games, plural intelligence, Early ChildhoodReferencesArmstrong, Thomas. Smart Baby’s Brain, Merangsang Kegeniusan Anak di Tiga Tahun Pertama. Jakarta: Prestasi Pustaka Publisher. 2003 Auryn, Virzara. How to Create a Smart Kids, Seri Kecerdasan Anak, Jakarta: Penerbit Katahati. 2007Bredekamp, Sue dan Copple. Developmentally Approriate Practise in Early Childhooh Program, USA: NAECY, 1992Bruce, T dan Maggit C. Child Care & Education, USA: Hodder & Stoughton A Member of Hodeder Headline Group. 1999Budiwanti, Erni. Islam Sasak, Yogyakarta: LKIS. 2000Essa, Eva L. Introduction to Early Childhood Education, 4th Edition, Canada: Thomson Delmar Learning. 2003.Fathurohman, O. (2017). Hakikat Bermain Dan Permainan Anak Usia Dini Di Pendidikan Anak Usia Dini (PAUD). Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(1), 27–36.Fitriyani, F. N. (2017). Perkembangan Bermain Anak Usia Dini. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 2(2), 125–140.Gopink, Alison. Andrew N Meltzoff. dan Patricia K Kuhl. Keajaiban Otak Anak. Jakarta: Mizan Mizan Media Utama. 2007Gunawan, Adi W. Genius Learning Strategy,. Jakarta: PT Gramedia Pustaka Utama. 2003 Hainstoock, Elizabeth G. Metode Pembelajaran Montessori untuk Anak Pra Sekolah, Jakarta: Pustaka Delapratasa. 1999Hidayatullah,Ahmad. Pendidikan Anak Muslim, Pendekatan Praktis Aplikatif Berdasarkan Nilai-Nilai Islam dan Teori Pendidikan Modern. Jakarta: Penerbit Fikr Rabbany Group. 2008Huliyah, M. (2016). Hakikat Pendidikan Anak Usia Dini. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 1(1), 60–71.Imroatun, I. (2014). Permainan Tradisional Sebagai Pembelajaran Kecakapan Sosial Bagi Anak Usia Dini. Jurnal Sains Psikologi, 3(1), 1–11.Jensen, Eric. Memperkaya Otak, Cara Memaksimalkan Potensi Setiap Pembelajar. Jakarta: PT Indeks. 2008Lukman, Lalu. Pulau Lombok dalam Sejarah Ditinjau dari Aspek Budaya. TT:TP. 2008Makaminan, Makagiansar. Saling Asih, Saling Asuh, Saling Asah. Jakarta: CSIS. 2002Manan, Imran. Dasar-Dasar Sosial Budaya Pendidikan. Jakarta : P2LPTK. 1989Margaret E. dan Bell Gredler. Belajar dan Membelajarkan. Jakarta: CV Rajawali. 1991Moleong. Metodology Penelitian Kualitatif. Bandung: Rosdakarya. 2005 Musfiroh, Tadkiroatun. Bermain Sambil Belajar dan Mengasah Kecerdasan. Jakarta: Depdiknas. T.t. Nusa Tenggara Barat. Sejarah Daerah Nusa Tenggara Barat. Mataram: T.P. 2002Pusat Penelitian Sejarah dan Budaya Nusa Tenggara Barat. Adat dan Upacara Perkawinan Daerah NTB, Mataram. T.P. 1996Nusa Tenggara Barat. Pengkajian Nilai Budaya. Naskah Babad Lombok, Mataram: T.P. 1999Prihantoro, A., & Hidayat, F. (2019). Melakukan Penelitian Tindakan Kelas. Ulumuddin : Jurnal Ilmu-Ilmu Keislaman, 9(1), 49–60.Santoso, Sugeng. Pendidikan Anak Usia Dini. Jakarta: Penerbit Citra Pendidikan. 2004.Santrock, John W. Life Span Development, USA: Times Mirror Higher Education Group. 1997Semiawan, Conny. Penerapan Pembelajaran Anak. Jakarta: Indeks. 2008.Setiani, R. E. (2019). Pemanfaatan Permainan Tradisional Dalam Penanaman Nilai-Nilai Kebangsaan Di TK Negeri Pembina 2 Purwokerto. Aṣ-Ṣibyān: Jurnal Pendidikan Anak Usia Dini, 4(1), 39–52.Silberg, Jackie. Brain Games for Toddlers, Jakarta: Penerbit Erlangga. 2004. Slee, Fhilip and Rosalyn Shut. Child Development: Thinking About Theories, London: Oxford University Press Inc. 2003.Stone, Sandra J. Playing A Kid’s Curriculum, Good Year Book; USA: Harper Collins Publishers. 1993.